Genetics of endometriosis: a comprehensive review. (3rd July 2019) - Deiana, Danilo; Gessa, Stefano; Anardu, Michela; Daniilidis, Angelos; Nappi, Luigi; D'Alterio, Maurizio N.; Pontis, Alessandro; Angioni, Stefano
Abstract: This review aimed to critically evaluate the review, observational, cohort, and case–control studies performed so far in order to assess the association between endometriosis and genetics. The search strategies used included an online search of the MEDLINE database and a manual search of relevant publications and reviews. Additional reports were collected by systematically reviewing all references from the retrieved papers. Family studies have long suggested that genetic factors play a role in the etiology of endometriosis. Nevertheless, until now, studies on candidate genes have revealed inconsistent and contradictory evidence, leading to more questions rather than clear answers. It is possible that recent technological improvements in genetic evaluation could allow for a better understanding of the pathogenic mechanisms of endometriosis in the near future.